Association between interleukin-8 levels and chronic periodontal disease: A PRISMA-compliant systematic review and meta-analysis. Issue 22 (June 2017) - Finoti, Livia S; Nepomuceno, Rafael; Pigossi, Suzane C; Corbi, Sâmia CT; Secolin, Rodrigo; Scarel-Caminaga, Raquel M.
Abstract: Background: Current publications present contradictory findings regarding interleukin-8 (IL-8) levels in patients with chronic periodontitis (CP). This systematic review compile evidences of the IL8 mRNA and protein levels in gingival tissue, saliva, and gingival crevicular fluid (GCF) investigated in patients with CP. Moreover, 2 meta-analyses were made focusing on the IL-8 levels in GCF and saliva of patients with or without CP. Methods: Electronic searches of the PubMed, Web of Science, and Scopus databases were conducted for publications up to February 2016 that investigated the levels of IL-8 detected in individuals with CP compared with health individuals. A total of 31 publications were included in the systematic review. For meta-analyses, the strength of association was calculated by pooled odds ratios with 95% confidence intervals using RevMan 5.1 software. Heterogeneity was examined using Higgins I-squared, tau-squared, and χ 2 tests. Results: In biopsies of gingival tissue of CP patients, all studies found higher IL8 mRNA levels, and the majority of studies showed higher IL-8 protein levels in this tissue of individuals with moderate to severe CP. Four studies investigating the IL-8 levels in saliva showed inconclusive results. In spite of some studies seemed to indicate higher levels of IL-8 in GCF of CP patients, the meta-analysis results showed significantly lower IL-8 levels (pg/μL) in GCF of CP patients in comparison with periodontally healthy subjects. Conclusions: We concluded that IL8 gene expression and IL-8 protein levels were higher in gingival tissues of CP patients when compared to periodontally health individuals. Meta-analysis of studies that measured IL-8 (pg/uL) in GCF found lower levels in CP patients. There are conflicting evidences regarding IL-8 levels in saliva.